Capital structure determinants of shariah-compliant firms / Zahariah Sahuddin ... [et al.] - Sahudin, Zahariah; Ismail, Zuraidah; Sulaiman, Saliza; Abd Rahman, Hamisah; Jaafar, Mohamad Nizam (Universit Teknologi MARA Cawangan Selangor, 2019)
This is a preliminary study developed to explore the determinants of capital structure of Shariah-compliant firms listed in Bursa Malaysia. This study is primarily motivated by the issue of the determinants still being inconclusive in the area of capital structure. The study is performed using the static models namely Pool Ordinary Least Square, Fixed Effect and Random Effect Model. Empirical analysis on the determinants reveals that country specific factor which is GDP and sector specific factor which is industry concentration are also significant in influencing the corporate financing decisions in this country along with firm specific factors such as efficiency, bankruptcy risk, profitability, tangibility, liquidity and size of the firm. The findings revealed that results are sensitive to models employed in the study. Nevertheless, the applicability of capital structure theories such as the trade-off theory, agency theory and pecking order theory diverge across sectors in Malaysia. The pecking order theory and agency theory are found to be the dominant theories governing the corporate financing decision in the country as well. It indicates strong evidence of hierarchy practised in firms’ financing decision. The finding on agency theory being dominant justifies the function of short-term debt as a controlling mechanism to mitigate the agency problem arises within firms across sectors